After the epizootic: Host–pathogen dynamics in montane tropical amphibian communities with high prevalence of chytridiomycosis. (11th August 2020) - C. LaBumbard, Brandon; Shepack, Alexander; Catenazzi, Alessandro
Abstract: The amphibian fungal disease chytridiomycosis, caused by Batrachochytrium dendrobatidis ( Bd ), poses a great threat to global amphibian biodiversity. In Peruvian cloud forests of the Kosñipata Valley of Manu National Park where chytrid infection is highly prevalent, we have monitored species‐rich amphibian communities since 1996. An epizootic of chytridiomycosis is thought to have caused the disappearance of 35% of species richness in the early 2000s. We investigated the post‐epizootic Bd prevalence and infection intensity within the remnant amphibian community from 2008 to 2015, and modeled Bd dynamics as a function of species, season, reproductive mode, life stage, and elevation. Prevalence was higher in 2012–2015 than in 2008–2009, but overall prevalence has remained fairly constant ( 50%) post‐epizootic. We also found that while prevalence decreased with elevation during the wet season, it generally increased with elevation during the dry season, potentially due to seasonal changes in temperature and precipitation. In aquatic habitats, Bd is likely maintained through a single, stream‐breeding, putative reservoir species (which survived epizootics, in contrast to other aquatic‐breeding species). The now‐dominant terrestrial‐breeding species allow Bd to persist and spread in terrestrial habitats, possibly through individual dispersal into naïve areas. We conclude that Bd prevalence in the Kosñipata Valley has stabilized over time, suggesting that Bd is now enzootic. Long‐term monitoring of host infection is important because temporal changes in prevalence and infection intensity can cause changes in host species richness and abundance, which in turn may alter the trajectory of host–pathogen dynamics. Abstract in Spanish is available with online material. Abstract : We investigated the post‐epizootic Batrachochytrium dendrobatidis (Bd) prevalence and infection intensity within the remnant amphibian community from the Kosñipata Valley of Manu National Park, Peru. Patterns of seasonal fluctuations in Bd are maintained through a putative aquatic reservoir and susceptible terrestrial hosts. We conclude that Bd prevalence in the Kosñipata Valley has stabilized over time, suggesting that Bd is now enzootic. Abstract : La quitridiomicosis, causada por el hongo Batrachochytrium dendrobatidis ( Bd ), es una amenaza global para la biodiversidad de anfibios. En los bosques nublados del valle de Kosñipata, Parque Nacional del Manu donde la infección por Bd es muy prevalente, hemos monitoreado comunidades de anfibios durante casi dos décadas. Investigamos la distribución y prevalencia post‐epizoótica de Bd de 2008 a 2015, y modelamos la prevalencia de infección mediante regresión logística en función de las especies, el período de muestreo, el modo reproductivo, la etapa de vida, la elevación y las interacciones entre pares de factores. La prevalencia fue mayor en el periodo 2012–2015 que en 2008–2009, pero la prevalencia general se ha mantenido bastante constante ( 50%) post‐epizoótica. La interacción entre la elevación y el período de muestreo reveló que, si bien la prevalencia disminuyó con la elevación durante la estación húmeda, generalmente aumentó con la elevación durante la estación seca, quizás debido a cambios estacionales en temperatura y precipitación. En ambientes acuáticos, Bd probablemente se mantiene a través de una única especie reservorio de reproducción lótica (la cual sobrevivió a las epidemias de Bd en contraste con la mayoría de las otras especies de reproducción acuática), mientras que las especies de desarrollo directo y reproducción terrestre son ahora dominantes y permiten que Bd persista y se disemine en ambientes terrestres del bosque nublado, posiblemente a través de la dispersión juvenil. Concluimos que la prevalencia de Bd en el valle de Kosñipata se ha estabilizado a lo largo del tiempo, lo que sugiere que Bd es enzoótico. El monitoreo a largo plazo de la infección en anfibios es importante porque los cambios temporales en la prevalencia y la intensidad de la infección pueden causar cambios en la riqueza y abundancia de las especies hospederas, que a su vez pueden alterar la trayectoria de la dinámica de la entre enfermedad y especies hospederas.